2012
DOI: 10.1093/ntr/nts081
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Change Explaining the Effect of Smoke-Free Legislation on Smoking Cessation in the Netherlands. An Application of the International Tobacco Control Conceptual Model

Abstract: Our findings support the ITC Conceptual Model, which hypothesized that policies influence smoking cessation through policy-specific variables and psychosocial mediators. Smoke-free legislation may increase smoking cessation, provided that it succeeds in influencing support for the legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…(2), and "…or are you not planning to quit?" (1) [6][7][8] . Respondents also had the opportunity to answer with "don't know".…”
Section: Intention To Quit (2013)mentioning
confidence: 99%
See 2 more Smart Citations
“…(2), and "…or are you not planning to quit?" (1) [6][7][8] . Respondents also had the opportunity to answer with "don't know".…”
Section: Intention To Quit (2013)mentioning
confidence: 99%
“…Smokers were asked: "Which of the following best describes you?" Response options were: "I don't want to stop smoking" (1), "I think I should stop smoking but don't really want to" (2), "I want to stop smoking but haven't thought about when" (3), "I really want to stop smoking but don't know when I will" (4), "I want to stop smoking and hope to soon" (5), "I really want to stop smoking and intend to in the next 3 months" (6), and "I really want to stop smoking and intend to in the next month" (7) 13 .…”
Section: Intention To Quit (2013)mentioning
confidence: 99%
See 1 more Smart Citation
“…In an older study we had found that Dutch non-smoking employees were more likely to ask co-workers not to smoke when they had more negative beliefs about the health consequences of passive smoking (Willemsen & De Vries, 1996). Compliance with smoking bans is higher if smokers are more supportive of them and if they are more aware of the health consequences of passive smoking (G. E. Nagelhout, de Vries, et al, 2012).…”
mentioning
confidence: 99%
“…Awareness of the importance of smoking cessation medication has not only increased among health professionals, but also among responsible persons in most western governments. New laws have been introduced banning smoking from public places in Europe, Australia, Canada and the USA, and, in addition, the public opinion of smoking has shifted to regard it as something that is not socially acceptable [27][28][29].…”
mentioning
confidence: 99%